An assessment of the readiness in pursuing diploma among pre diploma students in Universiti Teknologi Mara Pahang / Sharifah Zannierah Syed Marzuki … [et al.] - Syed Marzuki, Sharifah Zannierah; A. Halid @ Khalid, Rozieana; Ab. Halim, Roslilee; Yahya, Wan Kalthom; Ali, Roslina; Tajuddin, Norulhuda; Mustapha, Musramaini (2011)
This study focuses on the readiness of the pre diploma students in pursuing diploma in Universiti Teknologi MARA(UiTM) Pahang. It is essential for potential diploma students to be ready with the academic involvement in a higher learning institution like UiTM Pre diploma students in UiTM can be grouped into two separate fields namely commerce and science with different course duration. However, this study will only concentrate on pre diploma commerce students due to some limitations. This exploratory study will employ a survey design involving convenience sampling and data will be analyzed using descriptive statistics. The findings will be beneficial to academic staffs and policy makers in designing and implementing efficient pre diploma programmes.